Benefit sharing for BIM implementation: Tackling the moral hazard dilemma in inter-firm cooperation. Issue 3 (April 2017) - Zheng, Linzi; Lu, Weisheng; Chen, Ke; Chau, Kwong Wing; Niu, Yuhan
Abstract: Building information modeling (BIM) plays an important role in furthering value-creation of construction projects by advocating the inter-firm cooperation. When implementing BIM, however, individual firms inherently safeguard their self-interests regardless of the fact that inter-firm cooperation might reap joint BIM benefits for a project overall, which epitomizes a typical problem of moral hazards in project-based organizations. This paper develops an outcome-linked benefit sharing model that considers sharing joint BIM benefits among stakeholders including designers, contractors, and clients for tracking moral hazards therein. By modeling stakeholders' behaviors as evolutionary games within a principal–agent formalism, it has been deducted that (1) designers/contractors could be incentivized to cooperate had each stakeholder received a share higher than the quotient of BIM costs over value-creation in the design/construction phase; and (2) how joint BIM benefits can be more than noncooperation outcomes is key for clients to support BIM implementation. Highlights: This paper develops an outcome-linked benefit sharing model to promote BIM. The model tackles moral hazards in inter-firm cooperation. The model combines the game theory and the principal–agent formalism. The model incentivizes stakeholders' contributions to project value-creation.